Selenium-functionalized polycarbonate-polyurethane for sustained in situ generation of therapeutic gas for blood-contacting materials - Peichuang Li; Wanhao Cai; Kebing Wang; Lei Zhou; Shusheng Tang; Yuancong Zhao; Xin Li; Jin Wang (Smart Materials in Medicine, 2022)
Polyurethanes (PU) have been widely used in blood-contacting devices including indwelling implants and extracorporeal devices due to its good biocompatibility. However, the conventional PU also faces problems like thrombus formation and cell compatibility that could cause the treatment failure. In this study, a novel selenium-functionalized polycarbonate-polyurethane (PCU–SeSe) is developed based on the dynamic diselenide bond. Having diselenide bond-containing glycol as functional component, PCU-SeSe is endowed with glutathione peroxidase (GPx)-like catalytic activity, which could catalyze the release of nitric oxide (NO) continuously and controllably in the donor environment. This feature provides the materials with multiple functions from markedly suppressing platelet adhesion and activation, reducing the thrombogenesis, and enhancing the hemocompatibility. Meanwhile, PCU-SeSe could promote the growth of endothelial cell (EC) as well as significantly inhibit the growth of smooth muscle cell (SMC) and macrophage (MA) in vitro. The animal experiments including aortic implantation of sprague-dawley (SD) rats and stent implantation also demonstrate the abilities of endothelialization, thromboresistance, anti-inflammation, and anti-hyperplasia of PCU-SeSe in vivo. Overall, this study provides a new strategy for the designing of blood-contacting devices, which could be promising in the fabrication of cardiovascular biomaterials.